The Obesogenic Environment: Epigenetic Modifications in Placental Melanocortin 4 Receptor Gene Connected to Gestational Diabetes and Smoking - Franzago, Marica; Porreca, Annamaria; D’Ardes, Mario; Di Nicola, Marta; Di Tizio, Luciano; Liberati, Marco; Stuppia, Liborio; Vitacolonna, Ester (Frontiers in Nutrition, 2022)
Maternal metabolic insults as well as Gestational Diabetes Mellitus (GDM) influence the fetal health and may affect 'offspring's susceptibility to chronic diseases via epigenetic modifications. GDM, the most common metabolic disorder in pregnancy, can be considered the result of complex interactions between genetic and environmental factors. A critical point in this view is the identification of genes which are epigenetically modified under the influence of GDM. The melanocortin 4 receptor (MC4R) gene plays a crucial role in nutritional health by suppressing appetite and participating in energy control regulation. The correlations between pregnant 'women's metabolic profiles and placental epigenetic modifications of this gene have been poorly investigated. The aim of this study was to evaluate the effect of GDM and maternal clinical parameters at the third trimester of pregnancy to DNA methylation levels in the placenta at CpG sites of MC4R gene. Socio-demographic and clinical characteristics, Mediterranean diet adherence, smoking habits, and physical activity were assessed at the third trimester of pregnancy of 60 pregnant women, of which 33 with GDM. Clinical parameters of the newborns were recorded at birth. MC4R DNA methylation on maternal and fetal sides of the placenta was analyzed using bisulfite pyrosequencing. MC4R DNA methylation levels at CpG1 and CpG2 were lower on the fetal side of the placenta in GDM-affected women than in non-GDM-affected recruits (p=0.033). Moreover, DNA methylation levels on the maternal side at CpG1 were positively related to glucose concentration at 2-h oral glucose tolerance test (OGTT). On the other hand, CpG2 DNA methylation was positively related to both 1-h and 2-h during OGTT. Maternal DNA methylation level at CpG2 was also associated with low density lipoprotein cholesterol (LDL-C) at the third trimester of pregnancy (rho=0.340, p<0.05), while CpG1 methylation was negatively related to maternal weight variations at delivery (rho=-0.316, p<0.05). Significant associations between MC4R DNA methylation on the maternal side and lipid profile at third trimester of pregnancy in women smokers were found. Our results suggest that MC4R methylation profile in the placenta is related to maternal metabolic and nutritional conditions, potentially affecting foetal programming and the future metabolic health of the newborn.